2021
DOI: 10.1007/s11104-021-05100-x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and dynamic distributions of multiple elements and their species in the rice rhizosphere

Abstract: The biogeochemical cycles of elements from soils to plants are mainly governed by their rhizosphere processes. Understanding these processes is challenging and remains largely unresolved due to the complex interrelationships among different elements and due to a lack of appropriate techniques for simultaneous spatiotemporal monitoring. MethodsThis study employed an In-situ Porewater Iterative (IPI) sampler array (0-22 mm measurement distance every 1.7 mm, with a time interval of 3 to 10 days) to capture the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This aligns with previous reports in the rice rhizosphere. 29,54 The porewater As(III) and As(V) had a significant positive relationship with the arrA gene across the MAT−soil interface, which is likely because the arrA gene plays a crucial role in As mobilization in a reducing environment. 55 In contrast, As(III) showed a significant negative relationship with the aioA gene (Figure 6), supporting the importance of microbially mediated As(III) oxidation in micro-oxic environments in saturated soils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This aligns with previous reports in the rice rhizosphere. 29,54 The porewater As(III) and As(V) had a significant positive relationship with the arrA gene across the MAT−soil interface, which is likely because the arrA gene plays a crucial role in As mobilization in a reducing environment. 55 In contrast, As(III) showed a significant negative relationship with the aioA gene (Figure 6), supporting the importance of microbially mediated As(III) oxidation in micro-oxic environments in saturated soils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The aioA gene mediating As(III) oxidation was observed in this study, which has also been observed in the rhizosphere of many wetland plants. 29,61 The adsorption of As(V) by Fe(III) (oxyhydr)oxides and other soil solids is much higher than that of As(III), 50,62 hence oxidation of As(III) to As(V) will aid in reducing the release of As in soils. This shares a similar mechanism as using active oxidants such as Mn oxides and nitrate to immobilize As in soils.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For enzyme activity, reflecting root and/ or microbial activity, a new micro-zymography approach was developed by Ghaderi et al (2022). Yuan et al (2022) presented a new method for in-situ measurements of small-scale, spatially and temporally resolved sampling of soil pore water. For the quantification of exudation, Oburger et al (2022b, this issue) present a rapid and cheap method for determination of C in exudate samples, which can be used for samples obtained from hydroponics or from a soil-hydroponic hybrid approach.…”
Section: Plant-microbe-soil Interfacementioning
confidence: 99%